Academic News: Aaron Michael Butts, new Professor of Semitic Studies with a focus on Ethiopian and Eritrean studies at Universität Hamburg, with the project BeInf—Beyond Influence: The Connected Histories of Ethiopic and Syriac Christianity - Butts, Aaron (Aethiopica, 2022)
Academic News